Professional development success through educational supply chain attributes and industrial experience - Nur Shahida, Mat Ishah (2024)
Graduate mismatch results in an imbalance between what employers require of their workforce and what workers have in return, leaving thousands of people unable to advance in their careers. This also results in a lack of participation in workforce due to fewer job openings and higher competitions for jobs. Malaysia's educational supply chain must adapt to the changing nature and demand for labor and skills due to value chain globalization, demographic shifts, and technological advancements in order to produce more professional graduates. Therefore, the purpose of this study is to investigate the relationship between educational supply chain (EduSC) attributes, which include ethics and spirituality, data analysis skills, teamwork, language proficiency, thinking skills, knowledge, and professional development success. This study also examines the role of industrial experience as a moderator in the relationship between EduSC attributes and professional development success. The resource-based view theory was chosen as the underpinning theory to identify an individual's nature and resources that can be utilized to gain a competitive advantage over other individuals. This study adopts a descriptive research design with a quantitative research method to fulfill the research purposes. The target population for this study includes all employed individuals in Malaysia who work in the agriculture, industries, and services sectors. Based on G*Power analysis, 189 samples were selected using voluntary response sampling and then evaluated using partial least square structural equation modeling (PLS-SEM) using SmartPLS 4 software. According to the findings, ethics and spirituality, data analysis skills, and thinking skills are all positively related to professional development success. Yet, the findings demonstrate that industrial experience has no moderating effect on the relationship between EduSC attributes and professional development success. The outcomes of this study expanded the boundaries of knowledge regarding the EduSC and triggered awareness of stakeholders' involvement in the EduSC.